Sejarah Masuknya Islam Di Nusantara Melalui Wali Songgo Relasinya Dengan Masuknya Islam Di Maluku - Hajar Latuapo; Nirmala Nirmala (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
Islam did not leave a deep and widespread imprint on the local population of the archipelago, as the syncretism of Islam with pre-Islamic values subsequently gave rise to the "Javanese Religion." Consequently, the process of Islamization in the archipelago was not fully realized. Nurcholis Madjid's interesting statement, comparing Islam in India and Indonesia, states that although Islam in Southeast Asia has spread rapidly and become established, Indonesia, with a predominantly Muslim population, retains a romantic and nostalgic past for the glory of Hindu-Buddhist kingdoms, such as the relics of Borobudur and Prambanan, which have become national pride. A qualitative research approach was chosen because this study was conducted under natural conditions, depicting the actual conditions in society regarding the arrival of Islam in Southeast Asia (the archipelago) based on descriptions of situations or events, written or spoken words, sentences, images, and observable behavior, and directed at the individual's overall natural background.